Forest problems in Dohuk Governorate and the possibility of treating and Silviculture - Manati, Nibal; Wahid , Hossam (Al-Adab Journal, 2024)
Natural and artificial forests in Iraq in general and the study area in particular have multiple problems, some of which may be similar to the problems of forests found in other Arab countries and others may differ from them. The most important problems that led to the deterioration and decline of the natural forest area in Iraq can be limited to two groups of factors:Human (human) problems.Environmental and climate problems (natural).Forests in Dohuk Governorate are exposed to a series of human and natural problems that lead to the deterioration and decline of productivity. The most important of these problems are (human and natural fires, unjustified and ill-considered felling, overgrazing, shifting cultivation, urban expansion, climate change, and agricultural diseases and pests).